EKSPRESI RELATIF mRNA HIF-1α PADA JANTUNG, OTAK DAN DARAH TIKUS SELAMA INDUKSI HIPOKSIA SISTEMIK - Wanandi, Septelia Inawati; Dewi, Syarifah; Paramita, Reni (UI Scholars Hub, 2009)
Relative Expression of HIF-1α mRNA in Rat Heart, Brain and Blood During Induced Systemic Hypoxia. Hypoxia is a pathological condition in which the body as a whole or region of the body (tissue or cell) deprived of adequate oxygen supply. The transcriptional regulator hypoxia inducible factor-1 (HIF-1) is an essential mediator of O2 homeostasis. Unlike the β sub unit (HIF-1β), the activity of HIF-1α is controlled in an oxygen-dependent manner. It has been reported that the stability and expression of HIF-1α during hypoxia is remarkably higher than those under normoxic conditions.The aim of this study was to analyze the adaptive tissue responses during induced systemic hypoxia by comparation of relative expression of mRNA HIF-1α in rat heart, brain and blood. Twenty-five male Sprague Dawley rats were subjected to systemic hypoxia by placing them in the hypoxic chamber supplied by 8-10% of O2 for 0, 1, 7, 14 and 21 days, respectively. The relative expression level of HIF-1α mRNA in brain, heart and leucocyte cells were analyzed using quantitative RT-PCR assay (Real Time PCR) based on Pfaff’s formula. This study demonstrates that the increased of relative expression of HIF-1α mRNA during induced systemic hypoxia reached its maximum level at day 7 (in heart) or at day 14 (in brain), whereas in leucocyte cells the stimulation of HIF-1α expression was intensively maintained up to 21 days although the expression has reached the remarkably high level. We could conclude that HIF-1α as an oxygen sensing during systemic hypoxia has different capacity and sensitivity in brain, heart and blood tissues, due to the importance of oxygen homeostasis in each tissue